Study of the polymorphism rs3025058 of the MMP-3 gene and risk of pelvic organ prolapse in Brazilian women - Paula M. Maeda; Ana Paula S.L. Bicudo; Renata T.M. Watanabe; Thais S.M. Fonseca; Ricardo P. do Souto; César E. Fernandes; Emerson de Oliveira (Elsevier, 2019)
Objective: To analyze the polymorphism -1171 5A / 6A rs3025058 of the MMP-3 gene and the risk for pelvic organ prolapse (POP). Study Design: This is a cohort study. All patients attended the Urogynecology and Vaginal Surgery Section of the FMABC, from 2014 to 2016 and they were randomly recruited by the researchers at the first medical appointment. We selected 112 patients with symptomatic POPs and 180 patients with normal pelvic floors. The single nucleotide polymorphism (SNP) 5A / 6A of MMP-3 was determined by polymerase chain reaction (PCR) and analysis of the restriction fragments in both groups. Chi-squared test was used to compare the frequencies of polymorphisms between the groups. For those characteristics with statistical relevance, the crude odds ratio (OR) and its respective 95% confidence intervals were calculated; and, by logistic regression, were adjusted for each of the other characteristics, obtaining the adjusted OR. Hardy-Weinberg gene balance was determined using Pearson's Chi-squared test. Values of p < 0.05 were considered statistically significant. Results: Logistic regression of factors associated with genital prolapse showed that age (adjusted OR = 11.89, 95% CI, 3.53-40) and home delivery (adjusted OR = 9.645, 95% CI, 3.35-27.7) remained risk factors for genital prolapse in the sample studied. There was no statistically significant difference between the groups in the distribution of genotypes, even after calculating the contribution of the 5A recessive allele in the aggregated genotypes (5A / 5A + 5A / 6A). Conclusion: The polymorphism -1171 5A / 6A rs3025058 of the MMP-3 gene was not associated with the risk for POP. Age and home delivery were significantly associated with increased risk for the disease. Keywords: Pelvic organ prolapse, Gene polymorphism, MMP-3, Risk factors